HUBUNGAN ANTARA INDEKS MASSA TUBUH DENGAN KESEIMBANGAN PADA SISWA SMK KESEHATAN BHAKTI INSANI DEPOK - Khairunnisa Larasati (2022)
Background: Balance is a person's ability to maintain a position or posture in order to remain at the fulcrum. Excess weight will affect a person's balance because it affects the ratio of the thickness of body fat, muscle fibers, and bones. The purpose of this study was to determine whether there is a relationship between body mass index (BMI) and balance in students of SMK Kesehatan Bhakti Insani Depok. Design: This study uses a quantitative correlative design with a cross sectional approach. The sample in this study were students of SMK Kesehatan Bhakti Insani Depok with a total sample of 108 people. The parameters used in measuring static balance are one leg stand and dynamic balance using a modified bass test. Results: This study used SPSS 23 and the results obtained p = 0.01 on static and dynamic balance with the correlation coefficient between BMI and static balance of -0.586 while the correlation coefficient between BMI and dynamic balance of -0.862 conclusion there is a non-unidirectional relationship between BMI and static and dynamic balance.